POTENSI LABU SIAM SEBAGAI ANALGETIK - Sinatra, Jadeny; Siahaan, Jekson M. (Majalah Ilmiah METHODA, 2024)
Pain is an unpleasant emotional sensation. Pain can begin after inflammation and/or after tissue damage. The use of analgesic or anti-pain drugs so far has undesirable side effects, so people have begun to look for alternative traditional medicines as a substitute. One of the plants that can be used as an alternative medicine for analgesics is chayote (S. edule). The purpose of this review is to provide information about chayote as an analgesic. This study focused on reviewing articles on experimental studies conducted in vivo and its bioactive components.